Gut microbiota mediates positive effects of liraglutide on dyslipidemia in mice fed a high-fat diet - Zhao, Li; Qiu, Yue; Zhang, Panpan; Wu, Xunan; Zhao, Zhicong; Deng, Xia; Yang, Ling; Wang, Dong; Yuan, Guoyue (Frontiers in Nutrition, 2022)
Except for improving glycemic control, liraglutide, one of the glucagon-like peptide-1 receptor agonists, has exerted promising therapeutic effects for dyslipidemia. It has been proved that gut microbiota plays a dramatic role in regulating lipid metabolism. This study aims to explore whether liraglutide could improve dyslipidemia by modulating the gut microbiota in mice fed a high-fat diet (HFD). The C57BL/6 mice were fed a HFD to establish an animal model of dyslipidemia, and then administered with liraglutide or normal saline for 12 weeks. Indices of glucolipid metabolism were evaluated. Gut microbiota of the mice was analyzed by 16S rRNA gene sequencing. Compared with HFD group, liraglutide significantly alleviated weight, total cholesterol (TC) and low-density lipoprotein cholesterol (LDL) levels, meanwhile elevating high-density lipoprotein cholesterol (HDL) levels (all P<0.05). The gut microbiota analysis revealed that liraglutide greatly reduced the relative abundance of Firmicutes and augmented that of Bacteroidetes, with a concomitant drop in the Firmicutes/Bacteroidetes ratio. Meanwhile, liraglutide dramatically changed the overall composition, promoted the growth of beneficial microbes (Akkermansia, Lactobacillus, Parabacteroides, Oscillospira, etc), and inhibited the growth of harmful microbes (AF12, Shigella, Proteobacteria, Xenorhabdus, etc). Especially, the relative abundance of Akkermansia increased the most after liraglutide treatment. Correlation analysis suggested that TC and LDL were positively correlated with some harmful bacteria, and negatively associated with beneficial bacteria. This study confirmed that liraglutide had a certain therapeutic eﬀect on dyslipidemia in HFD-fed mice and could regulate the composition of the gut microbiota associated with lipid metabolism, especially Akkermansia. Thus, aﬀecting gut microbiota might be a potential mechanism of liraglutide in attenuating dyslipidemia.